Crime and housing in Malaysia: case study of Taman Melati terrace housing in Kuala Lumpur - Mohit, Mohammad Abdul; Elsawahli, Hanan Mohamed Hassan (Centre for Environment-Behaviour Studies (cE-Bs) and University Publication Centre (UPENA), UiTM, 2010)
Recently, Malaysia has adopted the “Safe city program”, which is focused towards creating violence and crime free cities. To achieve this, it is important to address crimes and disorder in residential areas. So far studies identified that changes in built environment and modifications in space design can impact residents and offenders’ perceptions of criminality. Various CPTED measures are employed to create defensible space. This paper examines the effect of physical design on the occurrences of crime in Taman Melati residential area of Kuala Lumpur City and tests the effects of the built environment on the possibility of crime reduction through physical planning measures.